Pengaruh Menghisap Slimber Ice Terhadap Intensitas Rasa Haus Pasien Gagal Ginjal Kronik Yang Menjalani Hemodialisa - Dasuki Dasuki; Buhari Basok (Universitas Muhammadiyah Ponorogo, 2019)
Abstract Patients with chronic kidney diseases who is going through a period of hemodialysis should keep solvent diet limitiedly for preventing over solvent between hemodialisis session, the consequence of limitation solvent was cause several effect on the body, one of which is the increase thirst. Management of thirst can be done throught sucking slimber ice. The purpose of this study to determine the effect of sucking slimber ice in intensity thirst on chronic kidney desases patient with hemodialysis. Design quasy experimental researchusing pre-post with control group. The sample in this study conductued on 68 respondents; 34 intervention and 34 control group. Who met the inclusion criteria. The results showed that the intensity of thirst in the intervention group decreased the average intensity of thirst was 3.03 with a significant value of p-value 0.000 (p 0.05) which means there is the effect of sucking slimber ice on the intensity of thirst. the control group in the findings of this study also experienced a decrease in the mean of 0.35 and a significant value of p-value = 0.005. It is recommended to make policies and standard operating procedures for thirst management for patients with chronic kidney failure who undergo hemodialysis by sucking slimber ice. Abstrak Pasien dengan penyakit gagal ginjal kronik yang menjalani hemodialisa harus mengontrol diet cairan untuk mencegah kelebihan volume cairan antara sesi hemodialisa, konsekuensi pembatasan cairan ini menimbulkan respon oleh tubuh, salah satunya dapat meningkatkan rasa haus. Manajemen intensitas rasa haus dapat dilakukan melalui menghisap ice cubes. Tujuan penelitian ini untuk mengetahui pengaruh menghisap ice cubes terhadap intensitas rasa haus pada penderita gagal ginjal kronis yang menjalani hemodialisa. Desain penelitian menggunakan quasi experimental pre-post with control group. Sampel dalam penelitian ini dilakukan terhadap 68 responden; 34 responden kelompok intervensi dan 34 responden kelompok kontrol yang memenuhi kreteria inklusi. Hasil penelitian didapat bahwa intensitas rasa haus pada kelompok intervensi terjadi penurunan intensitas rasa haus rerata adalah 3.03 dengan nilai signifikan p-value 0.000 (p 0.05) yang artinya terdapat pengaruh menghisap slimber ice terhadap intensitas rasa haus. kelompok kontrol pada temuan penelitian ini juga mengalami penurunan rerata adalah 0.35 dan nilai signifikan p-value= 0.005. Disarankan membuat kebijakan dan standar prosedur operasioanl manajemen rasa haus kepada penderita gagal ginjal kronik yang menjalani hemodialisa dengan menghisap slimber ice